Suppression of endothelial miR-22 mediates non-small cell lung cancer cell-induced angiogenesis - Yuan Gu; Gianni Pais; Vivien Becker; Christina Körbel; Emmanuel Ampofo; Elke Ebert; Johannes Hohneck; Nicole Ludwig; Eckart Meese; Rainer M. Bohle; Yingjun Zhao; Michael D. Menger; et al. (Elsevier, 2021)
MicroRNAs (miRNAs) expressed in endothelial cells (ECs) are powerful regulators of angiogenesis, which is essential for tumor growth and metastasis. Here, we demonstrated that miR-22 is preferentially and highly expressed in ECs, while its endothelial level is significantly downregulated in human non-small cell lung cancer (NSCLC) tissues when compared to matched nontumor lung tissues. This reduction of endothelial miR-22 is possibly induced by NSCLC cell-secreted interleukin-1β and subsequently activated transcription factor nuclear factor-κB. Endothelial miR-22 functions as a potent angiogenesis inhibitor that inhibits all of the key angiogenic activities of ECs and consequently NSCLC growth through directly targeting sirtuin 1 and fibroblast growth factor receptor 1 in ECs, leading to inactivation of AKT/mammalian target of rapamycin signaling. These findings provide insight into the molecular mechanisms of NSCLC angiogenesis and indicate that endothelial miR-22 represents a potential target for the future antiangiogenic treatment of NSCLC.